Redistributive Economies in Ancient Mesopotamian Society: A Case Study from the Isin-Larsa Period - Robertson, John Francis
Ph.D. diss.; Supervisor: J. D. Muhly. Order No. 8117842; Philadelphia-Istanbul archive of 483 texts, reign of Rim-Sin of Larsa; DissAbstr 42 (1981) 1268-A.